Plebeian modernity : social practices, illegality, and the urban poor in Russia, 1906-1916 - Gerasimov, Ilʹja Vladimirovič (2018)
Introduction: the subalterns speak out: Gerasim and the infamous – Writing degree zero, and beyond: reading social practices between the lines – The middle Volga city as the middle ground: urban plebeian society – The patriarchal metropolis: trespassing social barriers in late imperial Vilna – "We only kill each other": the anthropology of deadly violence and contested intergroup boundaries – The transformative social experience of illegality – Epilogue: Gerasim in power: a plebeian modernity